The Alexandrian Corinthian capital and its role in the evolution of the Corinthian order in Hellenistic, Roman, and late Roman architecture : a comparative study (3rd century BC-7th century AD) - Bassioni, Ahmed M. (Access archaeology., 2022)
The Alexandrian Corinthian Capital and its Role in the Evolution of the Corinthian Order in Hellenistic, Roman, and Late Roman Architecture discusses the evolution of the Corinthian capital in Antiquity and how this centred around Alexandria rather than Mainland Greece. It tackles the rise of the Corinthian capital in Classical Greece and its adaptation on in Hellenistic Alexandria. It describes the different designs of the Alexandrian capitals and later their adaptations throughout the Hellenistic world, the Roman Empire, and the early centuries of the Byzantine Empire and neighbouring countries. The book also shows how the Hellenistic versions of the Alexandrian capitals continued to be used in the Roman period both directly and indirectly.